Relevance of Al-Ghazali's Thought in Critical Thinking in the Perspective of 21st Century Education - Naratu Mulya, Annisa; Ulvya, Iflah; Aziza, Nur (Corolla International Conference, 2024)
This study aims to examine how the relevance of Al-Ghazali's thoughts, especially about critical thinking, can be applied in the context of 21st century education. Analyzing how the influence of Al-Ghazali's thinking in critical thinking in the 21st century perspective and the relevance of Al-Ghazali's thinking in critical thinking in the 21st century perspective. The method used is qualitative research with a library study approach or library research. The target population in this study are Al-Ghazali's works related to critical thinking, as well as modern studies on his contribution to education in the form of texts in the form of books, journal articles, dissertations, and other scientific documents that examine Al-Ghazali's thinking and 21st century education. The literature sample used in this study was taken by purposive sampling with the criteria taken in this study, namely first, primary and secondary works related to Al-Ghazali, second academic publications on the topic of 21st century education that contain the concept of critical thinking and third literature sources from reputable journals or scientific publishers. Data collection techniques are carried out by means of researchers conducting literature searches, literature selection, data classification. Data analysis was carried out in this study through the content analysis method (content analysis) researchers identified the main themes analyzed comparatively synthesized. He emphasized the importance of revelation and reason in the process of searching for truth, and divided knowledge into various levels that show human cognitive development. Al-Ghazali argued that intuition is the highest source of knowledge, which complements the use of logic in critical thinking.